Why is Canada's Price Level So Predictable? - Klyuev, Vladimir (IMF Working Papers; Working Paper ;, 2008)
One of the pioneers of inflation targeting (IT), the Bank of Canada is now considering a possibility of switching to price-level-path targeting (PLPT), where past deviations of inflation from the target would have to be offset in the future, bringing the price level back to a predetermined path. This paper draws attention to the fact that the price level in Canada has strayed little from the path implied by the two percent inflation target since its introduction in December 1994, and has tended to revert to that path after temporary deviations. Econometric analysis using Bayesian estimation suggests that a low probability can be assigned to explaining this behavior by sheer luck manifesting itself in mutually offsetting shocks. Much more plausible is the assumption that inflation expectations and interest rates are determined in a way that is consistent with an element of PLPT. This suggests that the difference between IT as it is actually practiced (or perceived) and PLPT may be less stark than what pure theoretical constructs posit, and that the transition to a fullfledged PLPT regime will likely be considerably easier than what was previously thought. The paper also shows that inflation expectations are a major driver of actual inflation in Canada, which makes it easier to keep inflation close to the target without large output costs.